2016
DOI: 10.1016/j.ctcp.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Slow breathing influences cardiac autonomic responses to postural maneuver

Abstract: Chronic slow breathing has been reported to improve Heart Rate Variability (HRV) in patients with cardiovascular disorders. However, it is not clear regarding its acute effects on HRV responses on autonomic analysis. We evaluated the acute effects of slow breathing on cardiac autonomic responses to postural change manoeuvre (PCM). The study was conducted on 21 healthy male students aged between 18 and 35 years old. In the control protocol, the volunteer remained at rest seated for 15 min under spontaneous brea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 32 publications
0
17
1
Order By: Relevance
“…; Vidigal et al . ). Compared to supine rest, standing increased and decreased the normalised LF and HF components, respectively (Task Force, ; Vidigal et al .…”
Section: Autonomic Control Of Heart Ratementioning
confidence: 97%
See 1 more Smart Citation
“…; Vidigal et al . ). Compared to supine rest, standing increased and decreased the normalised LF and HF components, respectively (Task Force, ; Vidigal et al .…”
Section: Autonomic Control Of Heart Ratementioning
confidence: 97%
“…Compared to supine rest, standing increased and decreased the normalised LF and HF components, respectively (Task Force, ; Vidigal et al . ). Accurate HRV analysis performed in healthy volunteers during head‐up tilt with gradual inclination changes showed only moderate heart rate increases but the normalised LF and HF components increased and decreased practically linearly and statistically significantly with the increasing tilt inclination from 0 to 90 deg (Montano et al .…”
Section: Autonomic Control Of Heart Ratementioning
confidence: 97%
“…In the study by Z hang et al [ 103 ], whilst they observed an increase in vagal power with slow breathing, sympathetic power did not significantly change; however, a change in the pattern of sympathetic bursts within breaths was observed (also reported by K oizumi et al [ 96 ], S eals et al [ 104 ] and L imberg et al [ 106 ]). On a similar note, V idigal et al [ 107 ] conducted an investigation into the effects of slow respiration (6 breaths per min) on autonomic response to postural manoeuvre. Slow breathing improved cardiac sympathetic and parasympathetic responsiveness to physical perturbations, which they suggested may be a result of augmented baroreflex sensitivity due to increased (initial) parasympathetic tone, and synchronisation of sympathetic and parasympathetic systems at 6 breaths per min.…”
Section: Cardiorespiratory Unitmentioning
confidence: 99%
“…In the context of fundamental research, the majority of data on cardiovascular and respiratory autonomic patterns is based on the analysis of parameters of HRV linear domain. On the basis of these results, we deduce the antagonism of autonomic effectors on RRI regulation (change of posture, i.e., supine vs. standing, Montano et al, 1994;Levy and Martin, 1996;Jasson et al, 1997) or their synergism of action (i.e., supine vs. standing with slow breathing, de Paula Vidigal et al, 2016). These interrelated patterns of sympathetic vs. parasympathetic activity on RRI regulation are not confirmed for non-linear domain dynamics (Sassi et al, 2015).…”
Section: Introductionmentioning
confidence: 74%
“…Also, the research on the orthostasis effect on HRV has been well-documented (De Souza et al, 2014;Zaidi and Collins, 2016;Valente et al, 2018) and is routinely used as a sensitive test for the evaluation of "physiological adaptive mechanisms" generated by the autonomic nervous system (head up tilt, Zygmunt and Stanczyk, 2010;Hoshi et al, 2019). Most of the studies that evaluate HRV in these physiological conditions (supine position, standing, supine position with 0.1 Hz breathing and standing with 0.1 Hz) focused on linear properties of HRV (Kabir et al, 2011;de Paula Vidigal et al, 2016;Javorka et al, 2018;Jha et al, 2018). However, non-linear properties quantify and explain up to 80% of total RRI variability (Vandeput, 2010) and reflect physiological mechanisms of multiinteracting cardiovascular control, mostly exerted through sympatho-vagal effectors operating in nonlinear fashion (de Godoy, 2016).…”
Section: Discussionmentioning
confidence: 99%